2015
DOI: 10.1136/thoraxjnl-2015-207428
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pulmonary matrix metalloproteinases and quantitative CT markers of small airways disease and emphysema in COPD

Abstract: BackgroundMatrix-metalloproteinases (MMPs) are proteolytic enzymes that can degrade the extra cellular matrix and drive tissue remodelling, key processes in the pathogenesis of COPD. The development of small airway disease has been identified as a critical mechanism in the early development of airflow obstruction but the contribution of MMPs in human disease is poorly characterised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
74
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 36 publications
6
74
0
1
Order By: Relevance
“…Studies have confirmed that CT densitometry demonstrates higher levels of emphysema in individuals with COPD as opposed to healthy smokers [31][32][33][34] There is also convincing evidence that CT densitometry has strong associations with airflow obstruction [10,[32][33][34][35][36][37][38][39][40][41] and analysis of over 4000 CT scans from the COPDgene study showed a strong negative correlation between %LAA <-950 and forced expiratory volume in 1 second (FEV1) and demonstrated increased emphysema with worsening GOLD severity [33]. CT densitometry also has strong associations with gas transfer (TLCO) [10,[35][36][37][38][39][40], six minute walk distance (6MWD) [32,36,40,42], BODE score [36,39,[43][44][45] and body composition [37,39,46,47].…”
Section: Emphysemamentioning
confidence: 85%
See 3 more Smart Citations
“…Studies have confirmed that CT densitometry demonstrates higher levels of emphysema in individuals with COPD as opposed to healthy smokers [31][32][33][34] There is also convincing evidence that CT densitometry has strong associations with airflow obstruction [10,[32][33][34][35][36][37][38][39][40][41] and analysis of over 4000 CT scans from the COPDgene study showed a strong negative correlation between %LAA <-950 and forced expiratory volume in 1 second (FEV1) and demonstrated increased emphysema with worsening GOLD severity [33]. CT densitometry also has strong associations with gas transfer (TLCO) [10,[35][36][37][38][39][40], six minute walk distance (6MWD) [32,36,40,42], BODE score [36,39,[43][44][45] and body composition [37,39,46,47].…”
Section: Emphysemamentioning
confidence: 85%
“…Few studies have investigated the link between gas trapping on CT and underlying mechanisms of disease. Our work has shown that CT markers of small airways disease are associated with a number of MMPs (-3, -7, -8, -9, -10 and 12), suggesting these play a key role in small airways remodelling in COPD [31]. The longitudinal changes and the distribution of gas trapping throughout the lungs are unknown.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, the finding in the Indian cohort of patients that MMP-10 is increased in the BALF of patients with TB compared with patients with other respiratory diseases indicates that there is some specificity in the increased MMP-10 concentrations in TB. MMP-10 activity has been implicated in other destructive pulmonary pathology, such as chronic obstructive pulmonary disease (41), and was associated with disease severity and prognosis in patients with idiopathic pulmonary fibrosis (42). Although our study implicated MMP-10 in the protease network up-regulated in TB, as MMP-10 was increased in respiratory secretions of patients with TB and at the gene expression level, we did not precisely define the cellular source.…”
Section: Discussionmentioning
confidence: 99%